Law on the Promulgation of Legal Documents of the National Assembly (12TH Legislature), 3RD session - The National Assembly (2008)
Legal documents are documents issued or jointly issued by state agencies in accordance with the authority, formats, sequence of steps and procedures prescribed in this Law or the Law on the Promulgation of Legal Documents of Peoples Councils and Peoples Committees, which includes common rules of conducts, which has compulsory effectiveness and the implementation of which is guaranteed by the Government to regulate social relations. Documents which are issued or jointly issued by state agencies but not in accordance with the authority, formats, sequence of steps and procedures prescribed in this Law or the Law on the Promulgation of Legal Documents of Peoples Councils and Peoples Committees are not legal documents.